1996
DOI: 10.1007/bf01273156
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin-like immunoreactivity, its molecular forms and monoaminergic metabolites in aged and demented patients with Parkinson's disease ? effect of L-Dopa

Abstract: There is some evidence that Parkinson's disease (PD) seems to be a heterogenous and generalized brain disorder reflecting a degeneration of multiple neuronal networks, including somatostatinergic neurons. Somatostatin-like immunoreactivity (SLI) and its molecular forms, high molecular weight form (HMV-SST), somatostatin-14 (SST-14), somatostatin-25/28 (SST-25/28) and Des-ala-somatostatin (Des-ala-SST), as well as homovanillic acid (HVA) and 5-hydroxyindoleacetic acid (5-HIAA) were estimated using HPLC and radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
3
12
0
1
Order By: Relevance
“…Our present results are in line with the significant increase of somatostatin-like immunoreactivity levels investigated in cerebrospinal fluid (CSF) from 23 patients with untreated early parkinsonian syndrome compared with control subjects (58). However, the opposite was found in CSF of patients with moderate or severe disease (59). Given our data, it may be possible that the increase in somatostatin is a compensatory mechanism trying to restore the DA levels.…”
Section: Discussionsupporting
confidence: 80%
“…Our present results are in line with the significant increase of somatostatin-like immunoreactivity levels investigated in cerebrospinal fluid (CSF) from 23 patients with untreated early parkinsonian syndrome compared with control subjects (58). However, the opposite was found in CSF of patients with moderate or severe disease (59). Given our data, it may be possible that the increase in somatostatin is a compensatory mechanism trying to restore the DA levels.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, many classical studies have shown variable degrees of decrease in the CSF HVA levels of PD patients compared with controls (Bernheimer et al, 1966; Guldberg et al, 1967; Johansson and Roos, 1967; Olsson and Roos, 1968; Gottfries et al, 1969; Curzon et al, 1970; van Woert and Bowers, 1970; Godwin-Austen et al, 1971; Mones et al, 1972; Papeschi et al, 1972; Pullar et al, 1972; Cox et al, 1973; Voto Bernales et al, 1973; Weiner and Klawans, 1973; Granerus et al, 1974; Davidson et al, 1977; Tabaddor et al, 1978; Lovenberg et al, 1979; Cunha et al, 1983; Mann et al, 1983; Cramer et al, 1984; Mena et al, 1984; Pezzoli et al, 1984; Burns et al, 1985; Gibson et al, 1985; Jolkkonen et al, 1986; Liu, 1989; Hartikainen et al, 1992; Strittmatter and Cramer, 1992; Chia et al, 1993; Mashige et al, 1994; Eldrup et al, 1995; Cheng et al, 1996; Strittmatter et al, 1996; Kanemaru et al, 1998; Goldstein et al, 2008). Engelborghs et al (2003) reported normal CSF DA and HVA, and decreased DOPAC levels.…”
Section: Neurotransmitters Neuromodulators and Related Substancesmentioning
confidence: 99%
“…Although levodopa treatment usually increases CSF HVA levels according to the majority of studies, this is not related with clinical improvement, with some exceptions (Durso et al, 1989), and pre-treatment CSF HVA levels does not predict levodopa response (Weiner et al, 1969; Chase, 1970; Curzon et al, 1970; Bertler et al, 1971; Casati et al, 1973; Cox et al, 1973; Mones, 1973; Weiner and Klawans, 1973; Granerus et al, 1974; Davidson et al, 1977; Liu, 1989; Nishi et al, 1989; Strittmatter et al, 1996; Antkiewicz-Michaluk et al, 1997; Durso et al, 1997; Krygowska-Wajs et al, 1997), except in one study which described an association between relatively high pre-treatment CSF HVA levels and a better response to levodopa (Gumpert et al, 1973). One study failed to show changes in ventricular CSF HVA levels after a single acute administration of levodopa (Moussa et al, 1992).…”
Section: Neurotransmitters Neuromodulators and Related Substancesmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with PD, a reduced brain level of somatostatin (SOM) is frequently observed (3)(4)(5)(6)(7). In old Wistar rats, an inhibition of brain SOM receptors can produce catalepsy (8), an animal model of parkinsonian bradykinesia and rigidity.…”
Section: Introductionmentioning
confidence: 99%